Optimization of data retrieval process for spectroscopic CO2 isotopologue ratio measurements. (5th April 2017) - Hovorka, J; Čermák, P; Veis, P
Abstract: In this work, a numerical model was developed for critical evaluation of the 13 CO2 / 12 CO2 ratio retrievals ( Δ δ value) from laser absorption spectra. The goal of the analysis was to determine the dependency of the absolute error of δ on different experimental parameters, in order to find the optimal conditions for isotopic ratio retrievals without using calibrated reference samples. In our study, the target precision for Δ δ was set at a level of ⩽ 1 %. The analysis was performed in the spectral range of the ν 1 + ν 3 CO2 band at 1.6 μ m, with the theoretical data originating from the HITRAN database. The proposed fitting algorithm allowed efficient compensation of the interference from weak transitions which are not well recognizable in a single spectrum. This effect was found to make a dominant contribution to the Δ δ value. Next, the optimal conditions for such an experiment regarding the pressure, spectral range and spectrum noise were found and discussed from the perspective of widely tunable laser applications.